Quality Assessment of Arabica and Robusta Coffee Under Different Post-Harvest Processing Methods Using Solar Dryer Technology - Anggia Fanesa; Maryanti Maryanti; Putri Mariska Fahmi Fahmi (Agricultural Science, 2026)
Post-harvest processing methods significantly influence coffee quality, yet traditional sun-drying techniques require 15-17 days and often result in inconsistent quality, particularly during rainy seasons. This study investigated the effects of four post-harvest processing methods (Natural, Full Wash, Semi Wash, and Honey) on quality characteristics of Arabica Sigararutang and Robusta Toraja coffee varieties using solar dryer dome technology. The research employed a factorial design with five replications for each treatment combination, resulting in 40 experimental plots. Coffee cherries were harvested from West Sumatra plantations at elevations of 1050-1150 masl for Arabica and 780-900 masl for Robusta. Quality assessment encompassed physical parameters (fresh weight, drying duration, color changes, dry weight, and yield), chemical parameters (moisture content, caffeine content, and pH level), and sensory parameters (color intensity, aroma, and overall acceptance) evaluated by certified panelists using 1-7 scoring scales. Results demonstrated that the Honey process yielded superior overall quality for both varieties, achieving highest sensory scores for color (5.30-5.35), aroma (5.36-6.21), and overall acceptance (3.81-4.64). The Semi Wash process exhibited the most efficient drying performance, requiring only 22.7-24.6 days compared to 33.4-32.9 days for Natural process. All treatments successfully achieved optimal moisture content (11.3-12.3%) using solar dryer dome technology. Arabica beans demonstrated higher fresh weight and caffeine content than Robusta across all processing methods. The Honey processing method combined with solar dryer dome technology represents an optimal approach for enhancing coffee quality and market competitiveness in small and medium-scale enterprises.